2020
DOI: 10.1038/s41598-020-58167-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of potato shoots, roots and stolons under nitrogen stress

Abstract: Potato crop requires high dose of nitrogen (N) to produce high tuber yield. Excessive application of N causes environmental pollution and increases cost of production. Hence, knowledge about genes and regulatory elements is essential to strengthen research on N metabolism in this crop. In this study, we analysed transcriptomes (RNA-seq) in potato tissues (shoot, root and stolon) collected from plants grown in aeroponic culture under controlled conditions with varied N supplies i.e. low N (0.2 milli molar N) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 61 publications
5
46
0
1
Order By: Relevance
“…In these three varieties of our results, the different biochemical and gene expression profiles in response to nitrogen deficiency were consistent with previous reports [ 30 32 ]. Jozefowicz et al [ 30 ] found that there are proteomic differences between two potato cultivars in response to N deficiency.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In these three varieties of our results, the different biochemical and gene expression profiles in response to nitrogen deficiency were consistent with previous reports [ 30 32 ]. Jozefowicz et al [ 30 ] found that there are proteomic differences between two potato cultivars in response to N deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…These DEGs were differentially expressed among cultivars, the difference in promoter or copy number might be the two key reasons for the differential response and regulation of in three cultivars of potato. Tiwari et al reported that most of the StNRT family members were down-regulated in roots under low N conditions [ 32 ], which was consisted with our results. The NRTs , NR and NiR are crucial for the acquiring N and its conversion to ammonia ( Fig 8 ) [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, we have reviewed application of integrated genomics, physiology and breeding approaches for improving NUE (Tiwari et al, 2018 ) and traits phenotyping under aeroponic in potato (Tiwari et al, 2020d ). Further, recent studies provide information about the genes and miRNAs associated with N stress in potato (Tiwari et al, 2020a , b , c ; Zhang et al, 2020 ). Potato is highly amenable to tissue culture and therefore transgenics protocols are well established.…”
Section: Results and Targets For Improving Nue In Potatomentioning
confidence: 99%
“…We summarize here potential candidate genes for improving NUE in potato based on the recent research (Tiwari et al, 2020a , b , c ; Zhang et al, 2020 ). Our studies indicate that in potato roots, high-affinity nitrate transporters are the key candidate genes for manipulation in N uptake and transport.…”
Section: Results and Targets For Improving Nue In Potatomentioning
confidence: 99%